1987
DOI: 10.1093/clinchem/33.12.2234
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of trace elements in lavage fluids from human bronchial alveoli by energy-dispersive x-ray fluorescence. 3. Routine analysis.

Abstract: We applied the energy-dispersive x-ray fluorescence technique to determination of trace elements in human bronchoalveolar lavage fluids. Our analysis of more than 200 samples allowed us to determine normal reference values, to be used in characterizing occupational exposure. These values are expressed both in nanograms per 1000 cells (of all kinds) and nanograms per 1000 macrophages to correlate lavage efficiency and dust content of the alveoli. The result expressed in milligrams per liter is not sufficient, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…In relation with the analytical techniques used in these studies, most elemental determinations in biofluids have been performed by atomic absorption spectroscopy (AAS) [81,82,83,87,91], particle-induced X-ray emission [95], energy-dispersive X-ray fluorescence [96], inductively coupled plasma atomic emission spectroscopy (ICP-AES) [24,74,79], or inductively coupled plasma mass spectrometry (ICP-MS) [73,76,77,80,84]. The main advantage of using an ICP-MS equipped with a triple quadrupole is the elimination of interferences by operating in either standard single quadrupole (SQ) mode or triple quadrupole (ICP-QQQ-MS).…”
Section: Metal Dyshomeostasis In Lung Cancer: Biofluids and Tissuesmentioning
confidence: 99%
“…In relation with the analytical techniques used in these studies, most elemental determinations in biofluids have been performed by atomic absorption spectroscopy (AAS) [81,82,83,87,91], particle-induced X-ray emission [95], energy-dispersive X-ray fluorescence [96], inductively coupled plasma atomic emission spectroscopy (ICP-AES) [24,74,79], or inductively coupled plasma mass spectrometry (ICP-MS) [73,76,77,80,84]. The main advantage of using an ICP-MS equipped with a triple quadrupole is the elimination of interferences by operating in either standard single quadrupole (SQ) mode or triple quadrupole (ICP-QQQ-MS).…”
Section: Metal Dyshomeostasis In Lung Cancer: Biofluids and Tissuesmentioning
confidence: 99%
“…These elements may be associated with the structure of kaolinite, which is a normal constituent of the soils where tobacco is cultivated and can accumulate in the leaves of the plant. Moreover, it was reported that Fe, Cu, Ni, Rb, Ti and Pb could be found in AM cytoplasm of healthy nonsmokers [20]. The results of a recent study by P .…”
Section: Discussionmentioning
confidence: 85%
“…20 ), PZAA (review in Pleban et al. 19 ), energy dispersive X-ray fluorescence, 30 AAS, 12,13,16,17,22 ETAAS, 10,14 ICP-OES, 10,15 and X-ray fluorescence (with Vitoux et al. 25 ).…”
Section: Resultsmentioning
confidence: 99%
“…12 ); these data indicate an initial disruption to the functioning of the body, 1 thus enabling action to be taken to prevent further deterioration in human health. Since then, research centers have conducted tests on the concentrations of elements, mainly in lymphocytes 1,1318 and erythrocytes, 1,10,1217,1939 although granulocyte 1 and platelets 1,25,40 data have also been obtained.…”
Section: Introductionmentioning
confidence: 99%